The E2F activators control multiple mitotic regulators and maintain genomic integrity through Sgo1 and BubR1 - Lee, Miyoung (Oncotarget, 2017)
The E2F1, E2F2, and E2F3a transcriptional activators control proliferation. However, how the E2F activators regulate mitosis to maintain genomic integrity is unclear. Centrosome amplification (CA) and unregulated spindle assembly checkpoint (SAC) are major generators of aneuploidy and chromosome instability (CIN) in cancer. Previously, we showed that overexpression of single E2F activators induced CA and CIN in mammary epithelial cells, and here we show that combined overexpression of E2F activators did not enhance CA. Instead, the E2F activators elevated expression of multiple mitotic regulators, including Sgo1, Nek2, Hec1, BubR1, and Mps1/TTK. cBioPortal analyses of the TCGA database showed that E2F overexpression in lobular invasive breast tumors correlates with overexpression of multiple regulators of chromosome segregation, centrosome homeostasis, and the SAC. Kaplan-Meier plots identified correlations between individual or combined overexpression of E2F1, E2F3a, Mps1/TTK, Nek2, BubR1, or Hec1 and poor overall and relapse-free survival of breast cancer patients. In MCF10A normal mammary epithelial cells co-overexpressing E2Fs, transient Sgo1 knockdown induced CA, high percentages of premature sister chromatid separation, chromosome losses, increased apoptosis, and decreased cell clonogenicity. BubR1 silencing resulted in chromosome losses without CA, demonstrating that Sgo1 and BubR1 maintain genomic integrity through two distinct mechanisms. Our results suggest that deregulated activation of the E2Fs in mammary epithelial cells is counteracted by activation of a Sgo1-dependent mitotic checkpoint.